Single-cell and spatial architecture of primary liver cancer - Zhou, Pei-Yun; Zhou, Cheng; Gan, Wei; Tang, Zheng; Sun, Bao-Ye; Huang, Jin-Long; Liu, Gao; Liu, Wei-Ren; Tian, Meng-Xin; Jiang, Xi-Fei; Wang, Han; Tao, Chen-Yang; et al. (Communications biology, 2023)
Primary liver cancer (PLC) poses a leading threat to human health, and its treatment options are limited. Meanwhile, the investigation of homogeneity and heterogeneity among PLCs remains challenging. Here, using single-cell RNA sequencing, spatial transcriptomic and bulk multi-omics, we elaborated a molecular architecture of 3 PLC types, namely hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (ICC) and combined hepatocellular-cholangiocarcinoma (CHC). Taking a high-resolution perspective, our observations revealed that CHC cells exhibit internally discordant phenotypes, whereas ICC and HCC exhibit distinct tumor-specific features. Specifically, ICC was found to be the primary source of cancer-associated fibroblasts, while HCC exhibited disrupted metabolism and greater individual heterogeneity of T cells. We further revealed a diversity of intermediate-state cells residing in the tumor-peritumor junctional zone, including a congregation of CPE + intermediate-state endothelial cells (ECs), which harbored the molecular characteristics of tumor-associated ECs and normal ECs. This architecture offers insights into molecular characteristics of PLC microenvironment, and hints that the tumor-peritumor junctional zone could serve as a targeted region for precise therapeutical strategies. A comprehensive multi-omic, single-cell, and spatial analysis provides further insight into the major cell types present in three types of primary liver cancer.